PMP Project Management Professional All-In-One Exam Guide - Phillips, Joseph (McGraw-Hill Education, 2021)
Complete coverage of all objectives in the 2020 release of the PMP exam--fully aligned with the PMBOK Guide®, Sixth Edition This comprehensive resource offers complete coverage of all the material included on the Project Management Professional exam. You'll find learning objectives at the beginning of each chapter, exam tips, practice exam questions, and in-depth explanations. Written by a leading project management consultant and trainer, PMP Project Management Professional All-in-One Exam Guide will help you pass the exam with ease and will also serve as an essential on-the-job reference. Covers all exam topics, including: People Processes Business Environment Agile Best Practices Knowledge Areas Online content includes: Practice exams--test yourself by PMP exam domain or take a complete exam Video training from the author Worksheets for Float, Earned Value, Time Value of Money Printable PMP memory card.